RESEARCH OF ELECTRICITY LOSSES IN ELECTRIC NETWORKS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The production, transmission and distribution as well as the consumption of electrical energy are processes that are connected and simultaneous. The processes of transmission and distribution of electrical energy from the place of production to the place of consumption is a process associated with certain losses that can be provoked by various factors.  Electrical loads are random in nature, but nevertheless they obey certain cyclicality in weekly, monthly, seasonal and annual aspects. In practice, it is necessary to determine and analyse them with sufficient accuracy. In this paper the error of electric power losses determination in distributed networks applying are analysed. An algorithm for calculate electric power losses with reading shape factor of load curves are made. For electrical networks differently configuration are applied the probability approach and investigate magnitude electric power losses.